A multimodalidade dos gêneros textuais em textos de livros didáticos - Ribeiro, João Paulo Samuel (2017)
This paper intends to examine texts from textbooks Portuguese visual language of multimodal texts in a book chapter Portuguese: languages, 6th grade: Portuguese; and the opening of a unit of the book Singular and plural, 9th grade: reading, production and language studies, according to the analytical composition principles proposed by the Grammar of Visual Design of Kress and van Leeuwen (1996), namely: information value , salience and framing.The study also examines whether the genres presented are worked in the activities of the books or just serve as mere support for other studies or mere illustration for aesthetic purposes. Although the books are multimodal and present studies with the pictures, we noticed an inclination of the images serve only as a means to work with the verbal text.